How Social Media Affects the Image of Religious Figures - Syaputra, Dedi; Anshori, Muhammad; al Rizkiyah, Khusnu; Nugroho, Dixi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The focus of this research is to understand how the public reaction to Habib Bahar's harsh da'wah style shapes his image in the eyes of the public, as well as how social media plays a role in strengthening or damaging the perception of religious figures. This research uses a qualitative approach with content analysis techniques, where the analysis unit includes text, images, and interactions on social media. Data was collected from various social media platforms and articles relevant to the phenomenon, which were then analyzed to identify emerging patterns, themes, and narratives. The results of the study show that although Habib Bahar's harsh da'wah style has attracted sharp criticism, this phenomenon actually strengthens his visibility and image in the eyes of his supporters. However, it also created a deep polarization among the public, with most audiences supporting his assertive approach, while others deemed the style not reflective of the morals of a religious figure. The implications of this study show that social media has an important role in shaping public perceptions, both positively and negatively, of religious figures, and the importance of balancing freedom of speech and social responsibility in communicating on digital platforms.